2020
DOI: 10.3762/bxiv.2020.137.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colorimetric detection of organophosphates with cysteamine capped gold nanoparticle sensors

Abstract: Nanozyme biosensors have the potential to provide high sensitivity, multiple functionality, and tunable activity. A facile colorimetric biosensor for the detection of organophosphates (OPs) using cysteamine capped gold nanoparticle probes (C-AuNPs) as enzyme mimics is proposed. Parathion ethyl (PE) a class of OPs is a potent insecticide that functions by inhibiting the acetylcholinesterase (AChE) in the nervous system of insects. The inhibition kinetics of AChE using PE enables the development of a PE sensor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Therefore, as displayed in Figure 4, Zhou's group developed a sensitive colorimetric strategy based on the principle for the detection of ACP and its inhibitor [94]. Besides, Shah et al found that Ch could result in the aggregation of cysteamine-capped gold nanoparticles (C-AuNPs) and weaken their ability to catalyze the oxidization of TMB [95]. Consequently, a C-AuNPs-based platform coupling with AChE was established to detect parathion-ethyl rapidly and sensitively.…”
Section: Generation Of Other Compoundsmentioning
confidence: 99%
“…Therefore, as displayed in Figure 4, Zhou's group developed a sensitive colorimetric strategy based on the principle for the detection of ACP and its inhibitor [94]. Besides, Shah et al found that Ch could result in the aggregation of cysteamine-capped gold nanoparticles (C-AuNPs) and weaken their ability to catalyze the oxidization of TMB [95]. Consequently, a C-AuNPs-based platform coupling with AChE was established to detect parathion-ethyl rapidly and sensitively.…”
Section: Generation Of Other Compoundsmentioning
confidence: 99%